Ethics and Morals of Christian Youth in the Digital World of the 5.0 Era: Analysis Based on Lawrence Kohlberg's Theory of Moral Development - Lumbantobing, Sarah; Siagian, Laurenz; Siramba, Febriyanti; Telaumbanua, Isa Umbu Riani (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2025)
The development of digital technology in the Society 5.0 era presents increasingly complex moral challenges for adolescents, including Christian adolescents who live amidst a current of ambiguous values, moral relativism, and virtual social pressures. In this context, moral education is no longer simply understood as the inheritance of norms or adherence to rules, but rather as a mentoring process that helps adolescents develop reflective moral reasoning rooted in faith. This article aims to examine Lawrence Kohlberg's theory of moral development as an analytical framework, analyze its implications for the moral formation of Christian adolescents in the digital era of Society 5.0, and formulate an integrative approach to Christian moral education that combines ethical reasoning and faith formation. This research uses a qualitative approach through literature review by analyzing relevant books and scientific articles in the fields of developmental psychology, moral education, and Christian education. The results of the analysis indicate that Kohlberg's theory makes an important contribution to understanding the stages of adolescent moral reasoning development, particularly in assessing ethical dilemmas rationally and reflectively. However, this theory has limitations when applied directly in the context of Christian faith because it tends to emphasize rationality and the principle of universal justice, while Christian ethics is rooted in a relationship with God, inner transformation, and the example of Christ. Therefore, this article emphasizes the importance of integrating Kohlberg's theory of moral development with Christian faith values through the role of Christian education in schools, the church as a faith community, and the family as the primary educational environment. This integration is expected to help Christian adolescents grow toward complete moral and spiritual maturity, enabling them to make responsible ethical decisions that reflect love, justice, and faith in the digital life of the Society 5.0 era.